Analisis Kinerja Aparatur Desa Dalam Meningkatkan Kualitas Pelayanan Publik Di Kantor Kelurahan Majaserta Di Kota Majalaya - Sali Maemunah, Imas; Maryono, Dicky (STIM-LPI Makassar, 2025)
This study aims to analyze the performance of the Majasetra Village apparatus in increasing public satisfaction. To find out what factors inhibit the performance of village apparatus in improving the quality of public services at the Majasetra Village Office, Majalaya City The method used in this study is descriptive qualitative. Data collection techniques in the study are observation, interviews, and documentation. Data analysis used in this study is data collection, data reduction, data presentation, and data verification conclusions. The conclusion of this study is that the performance of village apparatus in Majasetra Village is still less than optimal in terms of the length of the work process, as well as aspects of commitment to the less than good attitudes of some Majasetra Village employees. Regarding aspects related to employee performance targets and work behavior, namely quantity, quality, cost, orientation, integrity, discipline, cooperation and leadership, it has been said to be good. The factors that inhibit employee performance that researchers found were the differences in attitudes given by Majasetra Village employees in serving the community, which gave rise to the assumption that there was social discrimination. Furthermore, there is a lack of availability of facilities and infrastructure in the Majasetra sub- district office, all of which cannot be used, especially in technological devices